Chemical decellularization of porcine liver by two-stage treatment with surfactants and osmoregulators enhances preservation of liver extracellular matrix structure - A. D. Belova; E. A. Nemets; D. D. Filin; A. S. Ponomareva; L. A. Kirsanova; Yu. B. Basok; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2025)
Objective: to develop and investigate a tissue-specific matrix obtained using a modified chemical porcine liver decellularization regime in order to effectively increase preservation of extracellular matrix (ECM) structure, reduce decellularization time and improve purification of the ECM from cellular elements. Materials and methods. Original porcine liver was minced to obtain tissue fragments. Five decellularization regimes were used, with the concentrations and timing of surfactant treatments varied: 0.1% sodium dodecyl sulfate (SDS) and 0.1% or 1% Triton X-100, without and in combination with phosphate-buffered saline (PBS). The glycosaminoglycan (GAG) content of the resulting fragments was determined by lysing the samples for 12 hours in papain solution at +65 °C and then incubating them in 1,9-dimethylmethylene blue. DNA quantification was carried out using DNeasy Blood&Tissue Kit and Quant-iT PicoGreen dye. The morphology of the samples was studied using histological staining techniques. Cytotoxicity of the samples in vitro was evaluated on an NIH/3T3 mouse fibroblast culture by direct contact. Results. Treatment with 0.1% SDS for 2.5 hours with additional treatment with 1% Triton X-100 containing PBS for 21.5 hours (regime 4) increased GAG content to 11.66 ± 0.61 μg/mg compared to 0.68 ± 0.06 μg/mg (regime 5). The DNA content of samples obtained in regime 4 decreased from 99.75 ± 3.93 ng/mg to 14.93 ± 4.91 ng/mg after additional treatment with type I DNase, indicating that cellular components were effectively removed. This matrix showed no cytotoxicity. Conclusion. By optimizing the chemical decellularization regime for porcine liver, we were able to improve preservation of ECM structures, shorten decellularization time and effectively reduce the content of cellular elements. The modified decellularization protocol allowed to obtain a non-cytotoxic tissue-specific matrix with a low potential immunogenicity and a more preserved ECM structure and higher GAG content.